Profiling sociodemographic attributes and extreme precipitation events as mediators of climate-induced disasters in municipalities in the state of Minas Gerais, Brazil - Guedes, Gilvan; Andrade, Lara de Melo Barbosa; Silva, Cláudio Moises Santos e; Noronha, Kenya Valéria Micaela de Souza; Rodrigues, Daniele; Martins, Albert Smith Feitosa Suassuna (Frontiers in Human Dynamics, 2023)
Data indicate an increase in the number of natural disasters in Brazil, with the majority of these events in the Southeast Region – the richest, most populated, and urbanized in the country – occurring in the state of Minas Gerais. This study examines precipitation-related natural disasters recorded between 1991 and 2016 in Minas Gerais by identifying municipality profiles (encompassing the number of droughts, flash floods, and flooding events), their sensitivity to geophysical and extreme climatic exposure, and their relation to sociodemographic and infrastructure characteristics. We combine climate data on seven extreme rainfall indices with elevation data for each municipal seat. We obtained data on droughts, flash floods, and floods from the Center for Engineering and Civil Defense Research and Studies. Population and socio-sanitary characteristics were obtained from the 2010 Brazilian Demographic Census. First, we modeled the climatic-geo-socio-sanitary data using latent class analysis as a pure latent cluster model (LCM) without covariates on seven extreme precipitation indices coupled with altitude data. Subsequently, the LCM was used to identify precipitation-related disaster clusters, including clusters from the 1S-LCM as an active covariate (2S-LCM). Finally, we utilized sociodemographic and infrastructure variables simultaneously with the clusters from the 2S-LCM on an LCM without active covariates (3S-LCM). Our results show an increase in precipitation-related disasters in Minas Gerais, with municipalities located in the northern part of the state being particularly affected. The state registered 5,553 natural disasters in this period, with precipitation-related disasters representing 94.5% of all natural disasters. The 1S-LCM identified four homoclimatic zones, encompassing a low-altitude dry zone, a relatively low-altitude intermediately wet zone, a relatively high-altitude intermediately wet zone, and a high-altitude wet zone. The 2S-LCM produced four precipitation-related disaster classes, denominated low risk, high risk of excess precipitation, intermediate risk of precipitation deficit and excess, and high risk of precipitation deficit. Our 3S-LCM shows that within semi-arid regions, cities with better infrastructure and sociodemographic profiles are more resilient to droughts. In richer areas, floods are still a concern where incomplete urbanization transitions may undermine resilience to these events as they increase in intensity with the advance of climate change.